“Let Us All Enjoy the Fish”: Alternative Pathways and Contingent Histories of Collective Action and Governance Among Maritime Societies of the Western Peninsular Coast of Florida, USA, 100–1600 CE - Pluckhahn, Thomas J.; Jackson, Kendal; Rogers, Jaime A. (Frontiers in Political Science, 2022)
Ethnographers have ably documented the great extent and diversity of social institutions that contemporary fishers and shellfishers employ to collectively manage common property resources. However, the collective action regimes developed among ancient maritime societies remain understudied by archaeologists. We summarize research into the development and form of collective action among the maritime societies of the western peninsular coast of Florida, USA, drawing on our own recent work in the Tampa Bay area and previous work elsewhere in the region, especially the Calusa area to the south. Archaeological evidence suggests that collective action became more important in Tampa Bay in the first centuries CE, probably owing to a marine transgression that resulted in more productive estuaries. Groups here staked claims to productive estuarine locations through the founding of villages, the building of mounds, and the construction of relatively simple marine enclosures. Historically, these changes resulted in societies of relatively small scale and limited authoritarian government. In contrast, collective action developed later in the Calusa area, may have begun in relation to resource scarcity than plenty, and may been founded in kinship rather than in public ritual. Collective action in the Calusa area resulted in projects of greater scale and complexity, providing a foundation for more hierarchical and authoritarian social formations.